America, in space and time - Strong, Bryan; Bacon, Phillip; Conroy, William B. (Menlo Park, Calif. : Addison-Wesley Pub. Co., 1976)
Examines the history of the United States from early exploration to the present spotlighting several influential individuals.
Includes index.
Keywords: United States; United States -- History